Cardiac Involvement of Hepatitis B and C Virus Infection - Patwary, Mohammad Saifullah; Haque, KMHS Sirajul; Shoaib, Nusrat; Salehin, Khondaker Syedus; Hosan, ATM Iqbal (University Heart Journal, 2013)
Hepatitis B virus (HBV) and Hepatitis C virus (HCV) are the cause of many different forms of heart disease worldwide and yet few cardiologists are aware of it as an etiology of heart disease, or its treatment. The burden of HBV and HCV derived heart diseases are global, with a higher prevalence in Asia, Africa, and low- and middle-income countries. The study showed that in more than 10% of Japanese patients, their cardiomyopathies are associated with HCV infection. More recently, it is found in the USA that up to 15% of patients with heart failure with myocarditis have been associated HCV infection. In contrast, in China 79% of patients with hepatocellular cancer and 37% of hepatitis C patients have heart disease, as detected by measuring a proven and sensitive biomarker of heart disease, NT-proBNP. In Pakistan, 17% of hepatitis C patients have heart diseases, as measured by this metric (NT-proBNP). Based on these data, 3% of 6.6 billion (198 million) persons worldwide are infected with HCV and 1737% (3473 million) persons are suffering from HCV-derived heart diseases. These figures may be comparable to the number of patients with hepatitis C. HCV infection causes only hepatitis in some patients, only heart diseases in some patients, and both hepatitis and heart diseases in other patients. A global network is required to establish methods to detect heart diseases caused by infectious agents. Other goals for the network are the expansion of preventive and therapeutic programs in under privileged countries. DOI: http://dx.doi.org/10.3329/uhj.v8i2.16084 University Heart Journal Vol. 8, No. 2, July 2012